Psychological fitness tests for competitive performance forecasts - Yakovlev, B. P.; Babushkin, G. D.; Babushkin, E. G.; Tarasenko, I. B.; Usaeva, N. R.; Banshchikov, A. G. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to explore benefits of the competitive performance forecasting method based on the precompetitive psychodiagnostics data. Subject to the study were highly-skilled athletes representing swimming sprint, pistol shooting, weightlifting and speed skating sports. The subjects` mental fitness was tested and the test rates were used to split up them into Group 1 (n=10) with high mental fitness rates and Group 2 (n=15) with moderate mental fitness rates. We expected Group 1 being successful in attaining the training process goals and prize-winning in competitions; and Group 2 failing to fulfil the plans. Actual competitive performance data of both of the groups confirmed this assumption.